Wetland filler with heavy metal removal effect and preparation method thereof

CN122957952APending Publication Date: 2026-10-23NJTECH ENVIRONMENT TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611179047.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种具有重金属去除效果的湿地填料及制备方法,解决了现有技术中传统湿地填料吸附能力弱、寿命短、成本高、缺乏选择性及综合处理能力不足的问题

Benefits of technology

[0013]本发明的一种具有重金属去除效果的湿地填料的制备方法,通过火山石基体、铁锰氧化物功能层、巯基功能层和壳聚糖-生物炭复合包覆层的四级协同改性,构建"物理吸附-化学吸附-离子交换-氧化还原"多重机制。铁锰氧化物提供羟基,通过配体交换吸附含氧阴离子重金属(如As(V)、Cr(VI)),同时Fe3+/Mn4+可氧化As(III)为As(V)便于吸附;巯基(-SH)基团与软金属离子(Hg2+、Cd2+、Pb2+)形成稳定螯合物,选择性高;壳聚糖的-NH2和-OH基团螯合多种重金属离子,生物炭提供高比表面积和π-π作用。多级改性协同效应提升了填料的广谱性和吸附容量,重金属去除率可达Pb2+99.2%、Cd2+98.5%、As(V)96.8%(模拟污水中24小时处理效果),远超传统填料(<40%),同时兼容脱氮除磷功能。污泥减量:重金属去除无需化学沉淀,污泥产量减少35%(年减产120吨/万吨污水);无有害残留:改性剂为生物相容材料(壳聚糖、生物炭),避免二次污染。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122957952A_ABST
    Figure CN122957952A_ABST
Patent Text Reader

Abstract

The present application relates to the field of environmental protection, disclose a kind of wetland filler with heavy metal removal effect and preparation method, the present application is through the four-stage synergistic modification of volcanic rock matrix, iron-manganese oxide functional layer, mercapto functional layer and chitosan-biochar composite coating layer, constructs "physical adsorption-chemical adsorption-ion exchange-redox" multiple mechanism.Iron-manganese oxide is adsorbed by ligand exchange containing oxygen anion heavy metal, while As (III) can be oxidized to As (V);Mercapto and soft metal ions form stable chelate;Chitosan and biochar provide multiple chelating sites and high specific surface area.The removal rate of the filler to Pb 2+ 、Cd 2+ 、As (V) and other heavy metals is more than 96%, far more than traditional filler, and compatible denitrification and phosphorus removal function, sludge production is reduced by 35%, and the modifier is biocompatible material, no secondary pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmental protection technology, and in particular to a wetland filler with heavy metal removal effect and its preparation method. Background Technology

[0002] With the acceleration of industrialization and urbanization, heavy metal pollution (such as lead, cadmium, mercury, arsenic, and chromium) has become one of the core challenges in water environment management. Heavy metals are highly toxic, bioaccumulative, and non-degradable. Once they enter water bodies, they accumulate through the food chain, seriously threatening ecosystem health and human drinking water safety. According to the "China Ecological Environment Status Bulletin (2022)," 12.7% of surface water locations nationwide exceeded heavy metal standards, with the exceedance rate in water bodies surrounding industrial clusters exceeding 25%. Typical pollution sources include wastewater discharge from industries such as electroplating, mining, metallurgy, and electronics manufacturing. These sources are characterized by large fluctuations in heavy metal concentrations (1-500 mg / L), complex types (coexistence of multiple valence ions), and high treatment difficulty.

[0003] Constructed wetland technology is considered a potential pathway for heavy metal remediation due to its low cost, low energy consumption, and eco-friendly characteristics. However, traditional wetland fillers have fundamental shortcomings in heavy metal removal: traditional fillers (such as sand, gravel, and ordinary volcanic rock) have extremely low adsorption capacity for heavy metals, lack selective active sites, have small specific surface areas (<50 m² / g), and heavy metal adsorption capacities <10 mg / g (e.g., Pb). 2+ (Adsorption rate <30%), unable to distinguish between heavy metals and common cations (such as Ca). 2+ Mg 2+ The adsorption efficiency is greatly affected by water quality; the adsorption capacity of the packing material decays rapidly, saturating within 1-2 months at low concentrations of heavy metals (<5mg / L), and the pore blockage rate of the packing material exceeds 50% at high concentration shocks (>50mg / L), leading to system failure; it is sensitive to water quality fluctuations (pH, organic matter, ion competition), and the treatment effect is unstable, with the heavy metal adsorption rate decreasing by 60% when pH<5; traditional packing materials only target single pollutants (such as nitrogen and phosphorus removal) and lack the function of synergistic removal of heavy metals, requiring the addition of a chemical precipitation unit to wetland systems, increasing investment costs.

[0004] In addition, for industrial wastewater with high heavy metal content, traditional processes often use chemical precipitation to treat it. This process requires the addition of a large amount of chemical precipitation agents, which generates a large amount of chemical sludge. The subsequent sludge dewatering and hazardous waste disposal costs are high, and it is easy to cause secondary pollution. Summary of the Invention

[0005] The purpose of this invention is to provide a wetland filler with heavy metal removal effect and its preparation method, which solves the problems of weak adsorption capacity, short life, high cost, lack of selectivity and insufficient comprehensive treatment capacity of traditional wetland fillers in the prior art.

[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a wetland filler with heavy metal removal effect, comprising the following steps: The volcanic rock was crushed, soaked in hydrochloric acid to remove impurities, washed with deionized water until neutral, and dried to obtain pretreated volcanic rock. The pretreated volcanic rock was immersed in a mixed solution containing 0.2 mol / L Fe(NO3)3 and 0.1 mol / L Mn(NO3)2, the pH was adjusted with ammonia, the mixture was stirred in a water bath, allowed to stand and age, then removed, dried, and calcined to obtain volcanic rock loaded with iron and manganese oxides. The volcanic rock loaded with iron and manganese oxides was immersed in an anhydrous ethanol solution of 5% (v / v) 3-mercaptosilane coupling agent, reacted under nitrogen protection, removed, washed, and dried to obtain mercapto-functionalized volcanic rock. Chitosan was dissolved in acetic acid solution, and nano-biochar was added and ultrasonically dispersed to obtain a chitosan-biochar mixture. The thiol-functionalized volcanic rock was immersed in the chitosan-biochar mixture under vacuum impregnation, and after removal, a crosslinking agent solution was added dropwise for crosslinking. After drying, composite coated volcanic rock was obtained. The composite-coated volcanic rock was soaked in alkaline solution, washed with deionized water until neutral, and dried to obtain the wetland filler with heavy metal removal effect.

[0007] The volcanic rock has a particle size of 3-8 mm, the hydrochloric acid is 5% HCl, the soaking time is 2 hours, and the drying temperature is 105℃.

[0008] The solid-liquid ratio of the mixed solution is 1:5; the pH is adjusted to 8-9; the water bath stirring temperature is 60℃ and the stirring time is 2h; the standing aging time is 12h; and the calcination temperature is 300℃ and the calcination time is 2h.

[0009] The mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane with a concentration of 5% (v / v), and the solvent is anhydrous ethanol; the reaction temperature is 60°C, the reaction time is 6 hours, and the reaction is carried out under nitrogen protection; the washing agent is ethanol; and the drying temperature is 60°C.

[0010] The acetic acid solution is a 1% acetic acid solution; the chitosan is 2g, and the acetic acid solution is 100mL; the nano-biochar is 1g, with a specific surface area greater than 500m² / g; the ultrasonic dispersion time is 30min; the vacuum impregnation time is 2h; the crosslinking agent is at least one of glutaraldehyde, citric acid, or epichlorohydrin; the concentration of the crosslinking agent solution is 2%, and the crosslinking time is 2h; the drying temperature is 60℃.

[0011] The alkaline solution is a 0.1 mol / L NaOH solution, and the soaking time is 1 hour; the drying temperature is 60℃.

[0012] In a second aspect, a wetland filler with heavy metal removal effect is provided, using the preparation method of the wetland filler with heavy metal removal effect described in the first aspect, comprising a volcanic rock matrix; an iron-manganese oxide functional layer loaded on the surface of the volcanic rock matrix; a thiol functional layer grafted onto the surface of the iron-manganese oxide functional layer; and a chitosan-biochar composite coating layer covering the surface of the thiol functional layer.

[0013] This invention discloses a method for preparing a wetland filler with heavy metal removal effect. Through four-level synergistic modification of a volcanic rock matrix, an iron-manganese oxide functional layer, a thiol functional layer, and a chitosan-biochar composite coating layer, a multi-mechanism of "physical adsorption-chemical adsorption-ion exchange-redox" is constructed. The iron-manganese oxide provides hydroxyl groups, which adsorb oxygen-containing anionic heavy metals (such as As(V) and Cr(VI)) through ligand exchange, while Fe... 3+ / Mn 4+ As(III) can be oxidized to As(V), facilitating adsorption; thiol (-SH) groups react with soft metal ions (Hg) 2+ Cd 2+ Pb 2+ The process forms stable chelates with high selectivity; chitosan's -NH2 and -OH groups chelate various heavy metal ions, while biochar provides a high specific surface area and π-π interactions. The multi-stage modification synergistic effect enhances the broad-spectrum adsorption capacity and heavy metal removal rate, reaching up to Pb. 2+ 99.2%, Cd 2+ 98.5% purity and 96.8% As(V) (simulated 24-hour treatment effect in wastewater), far exceeding traditional packing materials (<40%), while also being compatible with nitrogen and phosphorus removal functions. Sludge reduction: Heavy metal removal eliminates the need for chemical precipitation, reducing sludge production by 35% (annual reduction of 120 tons / 10,000 tons of wastewater); No harmful residues: The modifier is a biocompatible material (chitosan, biochar), avoiding secondary pollution. Attached Figure Description

[0014] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.

[0015] Figure 1 This is a flowchart of a method for preparing a wetland filler with heavy metal removal effect provided by the present invention. Detailed Implementation

[0016] The embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, but should not be construed as limiting the present invention.

[0017] Please see Figure 1 In a first aspect, the present invention provides a method for preparing a wetland filler with heavy metal removal effect, comprising the following steps: S1 crushes the volcanic rock, soaks it in hydrochloric acid to remove impurities, washes it with deionized water until neutral, and dries it to obtain pretreated volcanic rock. The volcanic rock has a particle size of 3-8 mm, the hydrochloric acid is 5% HCl, the soaking time is 2 hours, and the drying temperature is 105℃.

[0018] S2 The pretreated volcanic rock is immersed in a mixed solution containing 0.2 mol / L Fe(NO3)3 and 0.1 mol / L Mn(NO3)2, the pH is adjusted with ammonia, the mixture is stirred in a water bath, allowed to stand and age, then removed, dried, and calcined to obtain volcanic rock loaded with iron and manganese oxides. The solid-liquid ratio of the mixed solution is 1:5; the pH is adjusted to 8-9; the water bath stirring temperature is 60℃ and the stirring time is 2h; the standing aging time is 12h; the calcination temperature is 300℃ and the calcination time is 2h.

[0019] S3 The volcanic rock loaded with iron and manganese oxides was immersed in an anhydrous ethanol solution of 5% (v / v) 3-mercaptosilane coupling agent, reacted under nitrogen protection, removed, washed, and dried to obtain mercapto-functionalized volcanic rock. The mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane with a concentration of 5% (v / v), and the solvent is anhydrous ethanol; the reaction temperature is 60°C, the reaction time is 6 hours, and the reaction is carried out under nitrogen protection; the washing agent is ethanol; and the drying temperature is 60°C.

[0020] S4 dissolves chitosan in acetic acid solution, adds nano-biochar, and disperses it ultrasonically to obtain a chitosan-biochar mixture; the thiol-functionalized volcanic rock is immersed in the chitosan-biochar mixture under vacuum impregnation, taken out, crosslinking agent solution is added dropwise for crosslinking, and dried to obtain composite coated volcanic rock; The acetic acid solution is a 1% acetic acid solution; the chitosan is 2g, and the acetic acid solution is 100mL; the nano-biochar is 1g, with a specific surface area greater than 500m² / g; the ultrasonic dispersion time is 30min; the vacuum impregnation time is 2h; the crosslinking agent is at least one of glutaraldehyde, citric acid, or epichlorohydrin; the concentration of the crosslinking agent solution is 2%, and the crosslinking time is 2h; the drying temperature is 60℃.

[0021] The crosslinking agent may also include citric acid, which forms a crosslinked network with chitosan through an esterification reaction.

[0022] An inorganic binder is also added to the chitosan-biochar mixture, wherein the inorganic binder is silicate and / or nano-silica.

[0023] The drying process also includes a high-temperature calcination treatment, with the calcination temperature not lower than 200°C, so that biochar and chitosan form chemical bonds through dehydration condensation or esterification reactions.

[0024] The nano-biochar is combined with chitosan through in-situ co-precipitation technology, so that the biochar particles and the chitosan matrix form stable covalent or ionic bonds.

[0025] The chitosan-biochar mixture also contains a phosphate material, which is at least one of hydroxyapatite, calcium phosphate, or sodium phytate.

[0026] The chitosan-biochar composite coating layer also contains phosphate material, which generates stable heavy metal phosphate precipitates through the reaction of phosphate ions with heavy metals.

[0027] The wetland filler also includes a modular encapsulation shell, which is used to fix the filler within a specific treatment unit to enhance its resistance to water erosion.

[0028] The crosslinking agent reacts with the amino groups on the chitosan molecular chain to form a crosslinked network. Considering that aldehyde crosslinking agents such as glutaraldehyde may undergo side reactions with thiol groups, in another embodiment of the present invention, the crosslinking agent may be a crosslinking agent inert to thiol groups (such as epichlorohydrin), or an environmentally friendly crosslinking agent such as citric acid that is crosslinked through esterification, or a physical coating method (such as freeze-drying to form a hydrogen bond network) may be used instead of chemical crosslinking to maximize the retention of the adsorption capacity of the thiol active sites.

[0029] S5 The composite-coated volcanic rock is soaked in alkaline solution, washed with deionized water until neutral, and dried to obtain the wetland filler with heavy metal removal effect.

[0030] The alkaline solution is a 0.1 mol / L NaOH solution, and the soaking time is 1 hour; the drying temperature is 60℃.

[0031] Specifically, this invention uses natural volcanic rock (particle size 3–8 mm) as the matrix and employs a four-stage synergistic modification process of "pretreatment activation → inorganic functional layer construction → organic functional layer grafting → composite coating reinforcement" to directionally impart the filler with resistance to various heavy metals (Pb). 2+ Cd 2+ Hg 2+ It has a high efficiency and selective removal capability for As(III / V) and Cr(VI).

[0032] Pretreatment of basic filler: volcanic rock is crushed to 3-8mm, soaked in 5% HCl for 2 hours to remove impurities, washed with deionized water until neutral, and dried at 105℃.

[0033] Iron-manganese oxide loading: The pretreated volcanic rock was immersed in a mixed solution containing 0.2 mol / L Fe(NO3)3 and 0.1 mol / L Mn(NO3)2 (solid-liquid ratio 1:5), the pH was adjusted to 8-9 with ammonia, stirred in a water bath at 60℃ for 2 h, allowed to stand for aging for 12 h, removed and dried, and calcined at 300℃ for 2 h (to form a Fe-Mn oxide coating).

[0034] Thiol functionalization: The above filler was immersed in an anhydrous ethanol solution of 5% (v / v) 3-mercaptopropyltrimethoxysilane and reacted at 60°C under nitrogen protection for 6 hours. After removal, it was washed with ethanol and dried at 60°C (to avoid high temperature damage to thiol groups).

[0035] Chitosan-biochar composite coating: Dissolve 2g of chitosan in 100mL of 1% acetic acid solution, add 1g of nano-biochar (specific surface area >500m² / g), and ultrasonically disperse for 30min; immerse the filler from step 3 into the mixture, vacuum impregnate for 2h, remove and add 2% glutaraldehyde solution for crosslinking for 2h, and dry at 60℃.

[0036] Activation treatment: Soak in 0.1 mol / L NaOH solution for 1 hour, wash with deionized water until neutral, and dry at 60℃ for later use.

[0037] Example: To further enhance the mechanical strength and water erosion resistance of wetland fillers, a natural polymer crosslinking agent and / or inorganic binder are introduced during the chitosan-biochar composite coating process in step 4. Specifically, in addition to glutaraldehyde, the crosslinking agent may also include citric acid; the citric acid forms a crosslinking network with the amino groups in the chitosan molecular chain through esterification, giving the material higher acid resistance and thermal stability. The inorganic binder is silicate and / or nano-silica, wherein silicate forms a composite structure with chitosan through hydrogen bonding and electrostatic interactions, while nano-silica enhances the mechanical strength and durability of the material at the microscale through nano-effects.

[0038] After the chitosan-biochar composite coating is completed, it can be subjected to high-temperature calcination. The high-temperature calcination temperature is not lower than 200℃, which utilizes thermal induction to promote the chemical reaction between the biochar particles and the chitosan matrix. This causes the hydroxyl and amino groups in the chitosan molecular chain to undergo dehydration condensation or esterification reactions with the carboxyl and phenolic hydroxyl groups on the surface of the biochar, generating a stable cross-linked structure. This significantly enhances the interfacial bonding strength and water erosion resistance of the composite material.

[0039] The nano-biochar can also be combined with chitosan through in-situ co-precipitation technology, so that stable covalent or ionic bonds are formed between the biochar particles and the chitosan matrix, effectively solving the problem of easy peeling and loss of biochar in traditional physical mixing methods.

[0040] To reduce the risk of secondary heavy metal pollution, a phosphate material is added to the chitosan-biochar mixture in step 4. The phosphate material is at least one of hydroxyapatite, calcium phosphate, or sodium phytate. The phosphate material contains phosphate ions (PO42-). 3- This material can react with heavy metal ions to induce the formation of extremely stable heavy metal phosphate precipitates, achieving in-situ passivation of heavy metals. This in-situ passivation not only significantly reduces the bioavailability and mobility of heavy metals, but also maintains excellent adsorption stability over a wide pH range, thus "locking" heavy metals inside the packing material and greatly reducing the risk of them being converted into free hazardous waste.

[0041] The wetland filler can also adopt a modular packaging scheme, which encapsulates the filler in a specific treatment unit to enhance its resistance to water erosion and avoid matrix loss, layer mixing or material runoff when there is extreme heavy rainfall or excessive water flow velocity.

[0042] In a second aspect, a wetland filler with heavy metal removal effect is provided, using the preparation method of the wetland filler with heavy metal removal effect described in the first aspect, comprising a volcanic rock matrix; an iron-manganese oxide functional layer loaded on the surface of the volcanic rock matrix; a thiol functional layer grafted onto the surface of the iron-manganese oxide functional layer; and a chitosan-biochar composite coating layer covering the surface of the thiol functional layer.

[0043] Furthermore, the chitosan-biochar composite coating layer also contains phosphate material, which generates stable heavy metal phosphate precipitates through the reaction of phosphate ions with heavy metals.

[0044] Furthermore, the wetland filler also includes a modular encapsulation shell, which is used to fix the filler within a specific treatment unit to enhance its resistance to water erosion.

[0045] In this embodiment, iron-manganese oxide: provides hydroxyl groups, which adsorb oxygen-containing anionic heavy metals (such as As(V), Cr(VI)) through ligand exchange; simultaneously, Fe 3+ / Mn 4+ It can oxidize As(III) to As(V), facilitating adsorption. The thiol group (-SH group) reacts with soft metal ions (Hg). 2+ Cd 2+ Pb 2+It forms stable chelates with high selectivity. Chitosan: -NH2 and -OH groups chelate various heavy metal ions; biochar provides high specific surface area and π-π interaction. Synergistic effect: Multi-level modification constructs a multiple mechanism of "physical adsorption-chemical adsorption-ion exchange-redox", improving broad-spectrum and capacity.

[0046] Beneficial effects: 1. Heavy metal removal rate: Pb 2+ 99.2%, Cd 2+ 98.5% and As(V) 96.8% (simulated 24-hour treatment effect in wastewater), far exceeding traditional packing materials (<40%); 2. Selective Adsorption: Through the synergistic effect of the Fe / Mn oxide layer (for As and Cr) and the thiol / amino functional layer (for Hg and Cd), highly selective adsorption of target heavy metals is achieved, avoiding adsorption with Ca. 2+ Mg 2+ Competition among interfering ions; 3. Broad-spectrum adaptability: Can simultaneously and efficiently remove Pb 2+ Cd 2+ Hg 2+ It contains multiple heavy metals such as As (III / V) and Cr (VI), which solves the single-function defect of traditional fillers.

[0047] 4. Sludge reduction: Compared with the traditional chemical precipitation process, the present invention removes heavy metals by adsorption through packing material without the need for additional chemical precipitation agents, reducing the production of chemical sludge by 35% (annual reduction of 120 tons / 10,000 tons of wastewater), thus reducing the subsequent sludge disposal costs.

[0048] 5. No harmful residues: The modifier is a biocompatible material (chitosan, biochar), avoiding secondary pollution.

[0049] The above-disclosed embodiments are merely one or more preferred embodiments of this application and should not be construed as limiting the scope of this application. Those skilled in the art can understand that implementing all or part of the above embodiments and making equivalent changes in accordance with the claims of this application still fall within the scope of this application.

Claims

1. A method for preparing a wetland filler with heavy metal removal effect, characterized in that, Includes the following steps: The volcanic rock was crushed, soaked in hydrochloric acid to remove impurities, washed with deionized water until neutral, and dried to obtain pretreated volcanic rock. The pretreated volcanic rock was immersed in a mixed solution containing 0.2 mol / L Fe(NO3)3 and 0.1 mol / L Mn(NO3)2, the pH was adjusted with ammonia, the mixture was stirred in a water bath, allowed to stand and age, then removed, dried, and calcined to obtain volcanic rock loaded with iron and manganese oxides. The volcanic rock loaded with iron and manganese oxides was immersed in an anhydrous ethanol solution of 5% (v / v) 3-mercaptosilane coupling agent, reacted under nitrogen protection, removed, washed, and dried to obtain mercapto-functionalized volcanic rock. Chitosan was dissolved in acetic acid solution, and nano-biochar was added and ultrasonically dispersed to obtain a chitosan-biochar mixture. The thiol-functionalized volcanic rock was then immersed in the chitosan-biochar mixture under vacuum impregnation. After removal, glutaraldehyde solution was added dropwise for crosslinking, and the mixture was dried to obtain composite-coated volcanic rock. Chitosan was dissolved in acetic acid solution, and nano-biochar was added and ultrasonically dispersed to obtain a chitosan-biochar mixture. The thiol-functionalized volcanic rock was immersed in the chitosan-biochar mixture under vacuum impregnation, and after removal, a crosslinking agent solution was added dropwise for crosslinking. After drying, composite coated volcanic rock was obtained. The composite-coated volcanic rock was soaked in alkaline solution, washed with deionized water until neutral, and dried to obtain the wetland filler with heavy metal removal effect.

2. The preparation method of the wetland filler with heavy metal removal effect as described in claim 1, characterized in that, The volcanic rock has a particle size of 3-8 mm, the hydrochloric acid is 5% HCl, the soaking time is 2 hours, and the drying temperature is 105℃.

3. The method for preparing the wetland filler with heavy metal removal effect as described in claim 1, characterized in that, The solid-liquid ratio of the mixed solution is 1:5; the pH is adjusted to 8-9; the water bath stirring temperature is 60℃ and the stirring time is 2h; the standing aging time is 12h; the calcination temperature is 300℃ and the calcination time is 2h.

4. The method for preparing the wetland filler with heavy metal removal effect as described in claim 1, characterized in that, The mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane with a concentration of 5% (v / v), and the solvent is anhydrous ethanol; the reaction temperature is 60°C, the reaction time is 6 hours, and the reaction is carried out under nitrogen protection; the washing agent is ethanol; and the drying temperature is 60°C.

5. The method for preparing the wetland filler with heavy metal removal effect as described in claim 1, characterized in that, The acetic acid solution is a 1% acetic acid solution; the chitosan is 2g, and the acetic acid solution is 100mL; the nano-biochar is 1g, with a specific surface area greater than 500m² / g; the ultrasonic dispersion time is 30min; the vacuum impregnation time is 2h; the crosslinking agent is at least one of glutaraldehyde, citric acid, or epichlorohydrin; the concentration of the crosslinking agent solution is 2%, and the crosslinking time is 2h; the drying temperature is 60℃.

6. The method for preparing the wetland filler with heavy metal removal effect as described in claim 1, characterized in that, The alkaline solution is a 0.1 mol / L NaOH solution, and the soaking time is 1 hour; the drying temperature is 60℃.

7. A wetland packing material with heavy metal removal effect, comprising the preparation method of the wetland packing material with heavy metal removal effect according to any one of claims 1-6, characterized in that, It includes a volcanic rock matrix; an iron-manganese oxide functional layer loaded on the surface of the volcanic rock matrix; a thiol functional layer grafted onto the surface of the iron-manganese oxide functional layer; and a chitosan-biochar composite coating layer covering the surface of the thiol functional layer.